2020
DOI: 10.1155/2020/4350274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Cooking on Quality of Riceberry Rice (Oryza sativa L.)

Abstract: Microwaves have been applied for cooking, warming, and thawing food for many years. Microwave heating differs from conventional heating and may cause variation in the food quality. This study determined the quality of Riceberry rice (Oryza sativa L.) after microwave cooking using various rice-to-water ratios at three power levels (360, 600, and 900 W). The texture of all microwave-cooked samples was in the range 162.35 ± 5.86 to 180.11 ± 7.17 N and was comparable to the conventionally cooked rice (162.03 N). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Therefore, it is important to find an effective processing method to reduce the in vitro digestibility of sorghum starch to promote the development of sorghum food. Thermal treatment of grain can improve its nutritional structure and reduce its in vitro digestibility (Chin, Therdthai, & Ratphitagsanti, 2020). Therefore, to reduce the in vitro digestibility of sorghum starch, sorghum may be heat-treated to alter its physicochemical properties to obtain better applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to find an effective processing method to reduce the in vitro digestibility of sorghum starch to promote the development of sorghum food. Thermal treatment of grain can improve its nutritional structure and reduce its in vitro digestibility (Chin, Therdthai, & Ratphitagsanti, 2020). Therefore, to reduce the in vitro digestibility of sorghum starch, sorghum may be heat-treated to alter its physicochemical properties to obtain better applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, Li et al ( 2019) stated that rice cooked by microwave had the lowest stickiness value. A different result was obtained by Chin et al (2020). The researchers determined that microwave-cooked rice had higher adhesiveness and chewiness than conventional cooking.…”
Section: Microwave Cookingmentioning
confidence: 96%
“…In addition, microwave processing may be manifested with excessive drip loss during thawing process (Oliveira et al, 2015) and requires appropriate mitigation techniques such as utilization of additives. Even though microwave cooking mostly result in improving the textural characteristics, certain rice varieties have shown higher chewiness, stickiness, and hardness values with microwave cooking and still requires careful optimization (Chin et al, 2020; Chusak et al, 2019).…”
Section: Challenges and Future Trendsmentioning
confidence: 99%
“…In a previous study by Chin et al . (2020), it was showed that the glycaemic index of rice cooked in microwave using various rice‐to‐water ratios at three power levels did not differ significantly compared to those processed using conventional methods.…”
Section: Introductionmentioning
confidence: 97%